Hubungan Antara Self Compassion Dan Psychological Well Being Pada Dewasa Awal Pasca Putus Cinta - Andi Annisa Kurnia; Asniar Khumas; Faradillah Firdaus (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Breakup is the end of an individual's emotional relationship with his partner. Individuals who experience a breakup can affect the individual's psychological well being. One of the factors that can improve psychological well being is self compassion. The purpose of this study was to determine the relationship between self compassion and psychological well-being in early adulthood after a breakup. This study uses quantitative methods. This research was conducted on 395 respondents, namely early adults aged 18-40 years who had been post-breakup obtained using accidental sampling. The results of this study indicate that there is a significant positive relationship between self compassion and psychological well being (r = 0.686; p = 0.000). The higher the individual's self compassion, the higher the individual's psychological well being. On the other hand, the lower the self compassion, the lower the psychological well being possessed by early adults after a breakup. The findings in this study have implications for early adulthood to increase self compassion so that they can overcome the negative effects of post-breakup in order to have good psychological well-being.